Czy Melpomena mówi po śląsku? O nurcie lokalnym w teatrze śląskim (PDF 1,76 MB) (Książnica Śląska, 2025)
The article discusses over a dozen theatrical performances stagedin Katowice’s Silesian Theatre in the 21st century. The author describes the relationship between the content of the performances andvarious forms of remembrance of important events in the history ofSilesia. The performances that are discussed are rooted in Silesian tradition and history, deal with topics important to the contemporariesand reach to local mythology, and at the same time show differenthistorical experiences and customs of the inhabitants of the Upper Silesia region. Are also described the differences between literary works(among others the prose of Szczepan Twardoch, an essay by ZbigniewRokita), complete biographies (e.g. Jerzy Kukuczka or Ryszard Riedl),and their stage productions. Moreover, the article reminds us ofhistorical performances that shaped the separate character of the Katowice scene and of performances played in other theaters (e.g. at theKorez Theatre, Ziemi Zagłębia Theatre or the Polish Theatre in Bielsko-Biała) to show the specificity of local Silesian theatre.